2009
DOI: 10.1016/j.ijsolstr.2009.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Buckling under the external pressure of cylindrical shells with variable thickness

Abstract: a b s t r a c tThis study focuses on the buckling of cylindrical shells with small thickness variations under external pressure. Asymptotic formulas in terms of the thickness non-uniformity parameter are derived by the combined perturbation and Bubnov-Galerkin methods. In addition to the analytic investigation based on the thin shell theory, a numerical analysis is also performed. Results from these formulas are discussed and compared with those obtained by other authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…It is noted that this result is consistent with the expression given by Nguyen et al [15]. So the accuracy of this analysis method is confirmed.…”
Section: Verification:supporting
confidence: 91%
See 2 more Smart Citations
“…It is noted that this result is consistent with the expression given by Nguyen et al [15]. So the accuracy of this analysis method is confirmed.…”
Section: Verification:supporting
confidence: 91%
“…If the cylindrical shell is simply-supported at its both ends, the boundary conditions will be [11,15]:…”
Section: Perturbation Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aghajari et al [6] presented experimental and numerical investigations for the buckling of thin cylindrical shells with stepwise variable wall thickness under uniform external pressure. Recently, Nguyen et al [7] employed the hybrid perturbation-Galekin method to consider the buckling problem of cylindrical shells with axisymmetric thickness imperfection in the shape of the axial buckling mode under the external pressure. They found that thin shells subjected to external were rather sensitive to thickness imperfection.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned analytical studies [1][2][3]7] on the buckling of thin-walled cylindrical shells with thickness imperfection treated simple axisymmetric modal thickness imperfection by employing the hybrid perturbation-Galekin method. However, this method is available for axisymmetric periodic thickness imperfection, and is very difficultly used to obtain buckling load even for this thickness imperfection [7], because the solution satisfying boundary conditions of compatibility equation needs to be solved exactly.…”
Section: Introductionmentioning
confidence: 99%